Exploring barriers to and facilitators of preventive measures against infectious diseases among Australian Hajj pilgrims: cross-sectional studies before and after Hajj. (June 2016) - Alqahtani, Amani S.; Wiley, Kerrie E.; Tashani, Mohamed; Willaby, Harold W.; Heywood, Anita E.; BinDhim, Nasser F.; Booy, Robert; Rashid, Harunor
Highlights: Pre-travel advice from general practitioners and travel agencies are the main facilitators of compliance. Not being aware of the availability of the information leads to poor coverage. Less than half of pilgrims were aware of the Hajj health recommendations issued by the Saudi Arabian Ministry of Health. Significant opportunities exist to improve pilgrims' awareness of preventive measures. Summary: Objective: For reasons that have yet to be elucidated, the uptake of preventive measures against infectious diseases by Hajj pilgrims is variable. The aim of this study was to identify the preventive advice and interventions received by Australian pilgrims before Hajj, and the barriers to and facilitators of their use during Hajj. Methods: Two cross-sectional surveys of Australians pilgrims aged ≥18 years were undertaken, one before and one after the Hajj 2014. Results: Of 356 pilgrims who completed the survey (response rate 94%), 80% had the influenza vaccine, 30% the pneumococcal vaccine, and 30% the pertussis vaccine. Concern about contracting disease at Hajj was the most cited reason for vaccination (73.4%), and not being aware of vaccine availability was the main reason for non-receipt (56%). Those who obtained pre-travel advice were twice as likely to be vaccinated as those who did not seek advice. Of 150 pilgrims surveyed upon return, 94% reported practicing hand hygiene during Hajj, citing ease of use (67%) and belief in its effectiveness (62.4%) as the main reasons for compliance; university education was a significant predictor of hand hygiene adherence. Fifty-three percent used facemasks, with breathing discomfort (76%) and a feeling of suffocation (40%) being the main obstacles to compliance. Conclusion: This study indicates that there are significant opportunities to improve awareness among Australian Hajj pilgrims about the importance of using preventive health measures.